Systematic review of Meckel's diverticulum in pregnancy. Issue 9 (21st June 2021) - Wong, Joshua You Jing; Conroy, Michael; Farkas, Nicholas
Abstract: Introduction: Meckel's diverticulum (MD) is the most common congenital malformation in the gastrointestinal tract. Limited up‐to‐date evidence is available regarding MD in pregnancy. We aim to review the available pertinent literature to help support clinical decision making and patient management in the future. Materials and Methods: The search term 'Meckel's diverticulum' was combined with 'pregnant' or 'pregnancy'. Database searches of EMBASE, Medline and PubMed were conducted. All papers published in English from 01/01/1990 to 01/01/2021 were included. Simple statistical analysis ( t ‐test) was performed. Results: Twenty‐seven cases were included. Average age = 26.9 years. Average gestation = 25.1 weeks. Occurrence: first trimester = 3.7%; second trimester = 48.1% and third trimester = 48.1%. Presenting symptoms: abdominal pain 88.9%; nausea/vomiting 59.3%; fever 18.5%; abdominal distension 18.5%; haematochezia 11.1%; constipation 11.1%; haematemesis 3.7%, diarrhoea 3.7% and asymptomatic 3.7%. Mean duration of preceding symptoms = 3.4 days. Diagnostic imaging modalities utilised: ultrasound = 40.7%; CT = 25.9%; MRI = 14.8%; abdominal X‐ray = 11.1% and endoscopy = 7.4%. All cases required definite surgical management: laparotomy = 65.4%; laparoscopy = 15.4%; C‐section = 19.2% and unreported = 3.8%. Main intra‐operative findings: perforated MD = 40.7%; intussusception with MD as a lead point = 11.1%; bleeding MD = 11.1%, inflamed MD = 11.1%; small bowel obstruction = 11.1%; gangrenous MD = 3.7%; volvulus = 3.7% and unspecified = 7.4%. Mean length from ileocolic junction = 51.7 cm. Average length of stay was 7.1 days. T ‐test ( p ‐value = 0.12) when comparing management strategy. Three maternal complications and two foetal mortalities. Conclusion: MD and associated pathology are difficult to diagnose in the pregnant cohort. Current imaging demonstrates low diagnostic accuracy and a deviation away from recognised nuclear medicine investigations. Surgery appears the definitive management with both open and laparoscopic approaches utilised. Significant maternal morbidity and foetal mortality are associated with this condition. Abstract : Meckel's diverticulum (MD) is the most common congenital malformation in the gastrointestinal tract. Limited up‐to‐date evidence is available regarding MD in pregnancy. We aim to review the available pertinent literature to help support clinical decision making and patient management in the future.